Parametric adaptive estimation and backstepping control of electro-hydraulic actuator with decayed memory filter. (May 2016) - Guo, Qing; Sun, Ping; Yin, Jing-min; Yu, Tian; Jiang, Dan
Abstract: Some unknown parameter estimation of electro-hydraulic system (EHS) should be considered in hydraulic controller design due to many parameter uncertainties in practice. In this study, a parametric adaptive backstepping control method is proposed to improve the dynamic behavior of EHS under parametric uncertainties and unknown disturbance (i.e., hydraulic parameters and external load). The unknown parameters of EHS model are estimated by the parametric adaptive estimation law. Then the recursive backstepping controller is designed by Lyapunov technique to realize the displacement control of EHS. To avoid explosion of virtual control in traditional backstepping, a decayed memory filter is presented to re-estimate the virtual control and the dynamic external load. The effectiveness of the proposed controller has been demonstrated by comparison with the controller without adaptive and filter estimation. The comparative experimental results in critical working conditions indicate the proposed approach can achieve better dynamic performance on the motion control of Two-DOF robotic arm. Abstract : Highlights: A parametric adaptive backstepping controller is proposed to improve the dynamic behavior of EHS under parametric uncertainties and unknown disturbance. The proposed parametric estimation law not only estimates the hydraulic parameters with uncertainties but also adapts the external load disturbance. The decayed memory filter is proposed to re-estimate these derivatives and the dynamic load to avoid large value of virtual control.